Odpowiedź :
Odpowiedź:
5/9 * 3/12 * 3/10 = 5/36 * 3/10 = 1/24
5/16 : 12/5 * 8/25 = 5/16 * 5/12 * 8/25 = 25/192 * 8/25 = 1/24
10/21 * 1/5 : 16/7 = 2/21 * 7/16 = 1/24
7/18 * 15/24 * 6/35 = 105/432 * 6/35 = 3/72 = 1/24
10 - 2 i 3/11 * 2 i 1/5 + 4/7 * 4 i 2/3 = 10 - 25/11 * 11/5 + 4/7 * 14/3 = 10 - 5 + 8/3 = 5 + 8/3 = 5 i 8/3 = 7 i 2/3 tu podkreśl mnożenie
(3/10 * 5/6 + 2 i 3/4) * 2/3 = (1/4 + 2 i 3/4) * 2/3 = 2 i 4/4 * 2/3 = 3 * 2/3 = 2 u podkreśl nawias
(5 i 1/3 : 2 i 2/3) + (12 - 1 i 5/7 * 5 i 5/6) = (16/3 * 3/8) + (12 - 12/7 * 35/6) = 2 + (12 - 10 = 2 tu podkreśl nawiasy
(5 - 2 i 1/4 * 5/9) * (2 - 2 i 2/3 : 1 i 3/5) = (5 - 9/4 * 5/9) * (2 - 8/3 * 5/8) =
(5 - 5/4) * (2 - 5/3) = (5 - 1 i 1/4) * (2 - 1 i 2/3) = (4 i 4/4 - 1 i 1/4) * (1 i 3/3 - 1 i 2/3) = 1 i 3/4 * 1/3 = 7/4 * 1/3 = 7/12 tu podkreśl nawiasy